Prevalence and determinants of unintended pregnancy among rural reproductive age women in Ethiopia - Melak Jejaw; Kaleb Assegid Demissie; Misganaw Guadie Tiruneh; Kaleab Mesfin Abera; Yawkal Tsega; Abel Endawkie; Wubshet D. Negash; Amare Mesfin Workie; Lamrot Yohannes; Mihret Getnet; Nigusu Worku; Adina Yeshambel Belay; et al. (Scientific Reports)
Abstract Despite growing utilization of family planning in Ethiopia, many pregnancies in rural areas are still unintended and unintended pregnancy remains a major global challenge in public and reproductive health, with devastating impact on women and child health, and the general public. Hence, this study was aimed to determine the prevalence and associated factors of unintended pregnancy in rural women of Ethiopia. This study used a 2016 Ethiopian Demography and Health Survey data. A total weighted samples of 974 reproductive-aged rural women were included in this analysis. Multilevel mixed logistic regression analysis was employed to consider the effect of hierarchal nature of EDHS data using Stata version 14 to determine individual and community level factors. Variables significantly associated with unintended pregnancy were declared at p-value < 0.05 with adjusted odds ratio and 95% confidence interval (CI). The prevalence of unintended pregnancy in rural women was 31.66% ( 95%CI 28.8%, 34.66%). Never had media exposure (AOR: 2.67, 95%CI 1.48, 4.83), don’t have work (AOR: 0.33, 95%CI 0.21, 0.52), being from household size of one to three (AOR: 0.44 95%CI 0.2, 0.96), being primiparous (AOR: 0.41, 95%CI 0.17, 0.99), women from poor families (AOR: 2.4, 95%CI 1.24, 4.56), lacking the intention to use contraceptive (AOR: 0.24, 95%CI 0.14, 0.44) were individual-level factors significantly associated with unintended pregnancy. Women from large central region (AOR: 4.2, 95%CI 1.19, 14.62) and being from poor community wealth status (AOR: 4.3, 95%CI 1.85, 10.22) were community-level factors statistically associated with unintended pregnancy. The present study prevalence of unintended pregnancy in rural women was relatively high. Maternal occupation, household size, media exposure, parity, women wealth, intention to use contraceptive, region and community level wealth were factors statistically associated with unintended pregnancy. Hence, demographer and public health practitioners has to give great emphasis on designing an intervention with implementation strategies to increase accessibility of media for reproductive-age women’s and improve women financial capacity, and strengthen maternal health services. These strategies helps to decrease adverse birth outcomes associated with unintended pregnancy in rural areas.